Applied Research on Policing for Police: the case of Cyprus - Constantinou, Angelo G. (Cham, Switzerland : Springer, 2021)
This brief discusses a series of empirical studies on policing in Cyprus, applying research to practice. It discusses police culture and tactics, and addresses politicized policing. Using primary data based on both quantitative and qualitative studies on the day-to-day issues of front-line policing in Cyprus, this volume will be of interest to academics, researchers and practitioners interested in comparative international policing, evidence-based policing, and contextualization of policing in Cyprus.
1. Introduction -- 2. ACAB -- 3. Echoes of police culture -- 4. Coping with police corruption -- 5. Discretion in police stops and searches -- 6. Police crowd control operations and the concealment of police identities -- 7. Rape myths and police attitudes -- 8. What do the police really do?- 9. The bitter end of politicized promotions- 10. Conclusion.
Includes bibliographical references and index.
Keywords: Law enforcement -- Cyprus -- Case studies; Law enforcement; Cyprus; Case studies